Haematopoietic stem cell gene therapy with IL‐1Ra rescues cognitive loss in mucopolysaccharidosis IIIA - Helen Parker; Stuart M Ellison; Rebecca J Holley; Claire O'Leary; Aiyin Liao; Jalal Asadi; Emily Glover; Arunabha Ghosh; Simon Jones; Fiona L Wilkinson; David Brough; Emmanuel Pinteaux; et al. (EMBO Molecular Medicine)
Abstract Mucopolysaccharidosis IIIA is a neuronopathic lysosomal storage disease, characterised by heparan sulphate and other substrates accumulating in the brain. Patients develop behavioural disturbances and cognitive decline, a possible consequence of neuroinflammation and abnormal substrate accumulation. Interleukin (IL)‐1β and interleukin‐1 receptor antagonist (IL‐1Ra) expression were significantly increased in both murine models and human MPSIII patients. We identified pathogenic mechanisms of inflammasome activation, including that disease‐specific 2‐O‐sulphated heparan sulphate was essential for priming an IL‐1β response via the Toll‐like receptor 4 complex. However, mucopolysaccharidosis IIIA primary and secondary storage substrates, such as amyloid beta, were both required to activate the NLRP3 inflammasome and initiate IL‐1β secretion. IL‐1 blockade in mucopolysaccharidosis IIIA mice using IL‐1 receptor type 1 knockout or haematopoietic stem cell gene therapy over‐expressing IL‐1Ra reduced gliosis and completely prevented behavioural phenotypes. In conclusion, we demonstrate that IL‐1 drives neuroinflammation, behavioural abnormality and cognitive decline in mucopolysaccharidosis IIIA, highlighting haematopoietic stem cell gene therapy treatment with IL‐1Ra as a potential neuronopathic lysosomal disease treatment.